2020
DOI: 10.1111/tesg.12427
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nature of Relatedness, or What Kind of Related Variety for Long‐Term Regional Growth

Abstract: We challenge the currently dominating static view of inter‐industry relatedness by investigating the evolution of relatedness linkages between Swedish industries during five sub‐periods between 1991 and 2010. Distinguishing between stable ties (present in all sub‐periods) and non‐stable ties (e.g. emerging, disappearing, etc.), we demonstrate that inter‐industry relatedness linkages change considerably over time. Furthermore, we show that these changes matter for how the co‐location of related industries (rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
9
0
1
Order By: Relevance
“…One early explanation for such mixed results was that potential for knowledge spillovers varies by sectors (Bishop and Gripaios 2010;Hartog, Boschma, and Sotarauta 2012;Innocenti and Lazzeretti 2019). In recent work another explanation has emerged which shows that relevance of related variety differs by type and development capabilities of regions (Firgo and Mayerhofer 2018;Kuusk and Martynovich 2021;van Oort, de Geus, and Dogaru 2015). Other scholars have taken a more critical stand demonstrating potential negative effects of related variety (Fitjar and Timmermans 2019).…”
Section: Related Variety Labour Mobility and Regional Employment Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…One early explanation for such mixed results was that potential for knowledge spillovers varies by sectors (Bishop and Gripaios 2010;Hartog, Boschma, and Sotarauta 2012;Innocenti and Lazzeretti 2019). In recent work another explanation has emerged which shows that relevance of related variety differs by type and development capabilities of regions (Firgo and Mayerhofer 2018;Kuusk and Martynovich 2021;van Oort, de Geus, and Dogaru 2015). Other scholars have taken a more critical stand demonstrating potential negative effects of related variety (Fitjar and Timmermans 2019).…”
Section: Related Variety Labour Mobility and Regional Employment Growthmentioning
confidence: 99%
“…Moreover, the focus on labour flows between industry-pairs makes a network measure more suitable than a system-wide entropy indicator. Also, many skill relatedness linkages are between 2-digit industry classification groups (Henning 2019;Kuusk and Martynovich 2021) and RSR allows this.…”
Section: Measuring Regional Related Varietymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, such measures of related variety disregard potential intertemporal dynamics in the relatedness linkages between various industries in the process of technological development (Martynovich 2016). Therefore, in long-term studies, it is more reasonable to employ measures of related variety based on revealed relatedness (Kuusk and Martynovich 2020). Following Neffke and Henning (2013), we claim that excessive exchange of labour between two industries signals overlapping skill requirements between them and indicates that these industries are related.…”
Section: Related Varietymentioning
confidence: 97%
“…This is because related activities represent a potential for new combinations on the one hand, and they share similar knowledge and skills that might enhance knowledge spillovers on the other hand. Related variety has often been shown to have a positive effect on regional growth (Boschma et al, 2014; Frenken et al, 2007; Kuusk and Martynovich, 2021; Tavassoli and Carbonara, 2014). Moreover, relatedness has been found to be a key input for regional diversification (Essletzbichler, 2015; Kogler et al, 2013; Muneepeerakul et al, 2013; Neffke et al, 2011).…”
Section: Relatedness In Good and Bad Timesmentioning
confidence: 99%